PERSONAL BRANDING SELEBGRAM MELALUI AKUN INSTAGRAM (STUDI DESKRIPTIF PADA AKUN @NADYAROSMANIA) - Nabila Triyani Putri (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Social media has taken a vital in Marketing Communication nowadays, especially instagram which becoming a one stop social media for its users to brand their self personally. celebgram in one of instagram’s market product, being a celebgram someone should have a strong Personal Brand which can be used to differ themself from others, that fact led celebgram to build Personal Branding. the purpose of this research is to find out Nadya Rosmania applied her Personal Branding as a celebgram through her instagram account @Nadyarosmania. Nadya use her speciality in fashion thus becoming an ambassador of Indonesia’s famous Fashion brand product which is, Zalora. the method used in this research is Descriptive Qualitative with Post-Positivism Paradigm, and reffered to Authentic Personal Branding Criteria. The Result of the research shows that Nadya has fulfilled the entire eleven components which is in the Authentic Personal Branding Criteria (Authenticity, Integritity, Consistency, Specialty, Authority, Difference, Relevancy, Visibility, Persistence, Goodwill and Performance).